Anjuran Dakwah Dalam Hadis Nabi Ballighu ‘Anni Walau Ayah Perspektif Ulama Hadis - Samadi; Heru Purnomo; Hotib (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the meaning and recommendations for da'wah in the hadith of the Prophet Muhammad SAW, Balligh? ‘ann? Walau ?yah, based on the perspectives of classical and contemporary hadith scholars. This study uses a qualitative method with a library research approach, where primary sources are taken from major hadith books such as ?a??? al-Bukh?r?, Sunan al-Tirmidh?, Sunan al-D?rim?, and Musnad A?mad bin ?anbal. The analysis was carried out through the takhrij al-?ad?th process to trace the chain of narration and text, followed by ma‘?n? al-?ad?th analysis to understand the contextual meaning based on explanations from scholars such as Ibn ?ajar al-‘Asqal?n?, Badr al-D?n al-‘Ain?, and al-Q??? al-Bay??w?. The results show that the hadith of Balligh? ‘ann? Meski ?yah is a valid hadith with a continuous sanad and a trusted narrator. The content of this hadith emphasizes that the obligation of da’wah is universal, not limited to scholars, but applies to every Muslim according to their knowledge and abilities. The hadith of Balligh? ‘ann? Meski ?yah not only functions as an invitation to da’wah but also as a basic principle for spreading knowledge and truth in Islam, upholding the values ??of honesty, truth, and justice.